Ecofriendly one-pot biosynthesis of indigo derivative dyes using CYP102G4 and PrnA halogenase - Namgung, Seyun; Park, Hyun A.; Kim, Joonwon; Lee, Pyung Gang; Kim, Byung Gee; Yang, Yung Hun; Choi, Kwon Young (Dyes and Pigments, 2019)
In this study, the biosynthesis of various indigoids with novel spectral features and antibacterial activities was investigated. First, 12 indole derivatives as substrates were biotransformed into functional indigoid dyes by E. coli cells expressing CYP102G4 hydroxylase. The indole derivatives included chloro (Cl-), nitro (NO2-), hydroxy (HO-), methoxy (CH3O-), methyl (CH3-), carboxy (COOH-), amino (NH3-), and cyano (CN-) indoles at the C4 to C7 positions. Interestingly, dramatic color shifts were observed from blue to red, green, purple, and even pink depending on the functional groups and their positions. Next, the biological and physical properties, antibacterial effects, and dying fastness of the prepared compounds were investigated and visually measured. Among the synthesized indigoid dyes, 6,6’-dichloroindigo and 5,5’-dichloroindigo showed the relatively higher cell growth inhibitory activity in the liquid phase. Finally, a one-pot producing strain which produced 7,7’-dichloroindigo from L-tryptophan using tryptophan-7-halogenase (PrnA) and CYP102G4 simultaneously was developed to overcome the disadvantages of uneconomical semi-synthesis through indole precursor feedstocks. The developed producing strain produced approximately 15.4 ± 1.4 mg/L of 7,7’-dichloroindigo in 24 h. To the best of our knowledge, this is the first report of the production of 7,7’-dichloroindigo in E. coli via a one-pot process.
Keywords: CYP102G4; Indigo derivatives; Indigoid dyes; Indole; PrnA; Antibacterial indigoid dye; CYP102G4; Indigo derivatives; Indole; PrnA